2019
DOI: 10.2903/j.efsa.2019.5860
|View full text |Cite
|
Sign up to set email alerts
|

Scientific opinion on the risks for animal and human health related to the presence of quinolizidine alkaloids in feed and food, in particular in lupins and lupin‐derived products

Abstract: The European Commission asked EFSA for a scientific opinion on the risks for animal and human health related to the presence of quinolizidine alkaloids (QAs) in feed and food. This risk assessment is limited to QAs occurring in Lupinus species/varieties relevant for animal and human consumption in Europe (i.e. Lupinus albus L., Lupinus angustifolius L., Lupinus luteus L. and Lupinus mutabilis Sweet). Information on the toxicity of QAs in animals and humans is limited. Following acute exposure to sparteine (ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 157 publications
1
69
0
Order By: Relevance
“…The toxicity of ZEA has attracted widespread attention due to the estrogenic effects of its metabolites. Over the past decade, both in vivo and in vitro studies have shown that ZEA has harmful effects on the reproductive systems of humans and animals [ 8 , 9 , 10 ]. Although studies have observed ZEA inducing autophagy and apoptosis in mammalian granulosa cells, the molecular mechanism of ZEA cytotoxicity remains unclear [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity of ZEA has attracted widespread attention due to the estrogenic effects of its metabolites. Over the past decade, both in vivo and in vitro studies have shown that ZEA has harmful effects on the reproductive systems of humans and animals [ 8 , 9 , 10 ]. Although studies have observed ZEA inducing autophagy and apoptosis in mammalian granulosa cells, the molecular mechanism of ZEA cytotoxicity remains unclear [ 3 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have shown that exposure to ZEA causes early puberty in children, endometrial adenocarcinoma, female breast cancer, and reduced testicular germ cells [ 5 , 6 ]. Meanwhile, in livestock production, low and high concentrations of ZEA have all been shown to have adverse effects, leading to hyperestrogenemia, abortion, and reproductive failure [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the assessment revealed the possibility of exposures for some consumer groups, resulting in MoE values <1, indicating a potential risk for these consumers. Additionally, the EFSA stated that there is indirect evidence of a possible transfer of QAs from feed into milk, due to the QAs’ weak basic nature, which makes milk a possible additional exposure source . However, until now, there has only been one published case report of possible QA intoxication in a human infant after its mother drank goat milk in early pregnancy .…”
Section: Introductionmentioning
confidence: 82%
“…The QAs exert their toxicity by inhibiting acetylcholine receptors and voltage-dependent ion channels in the central nervous system, on motor endplates and the peripheral autonomic nervous system, where the individual QAs appear to have different levels of toxicity . Common acute toxic exposure symptoms in humans and mammals include respiratory depression, vomiting, and tachycardia. , Some QAs, such as anagyrine, also show teratogenic properties and have been associated with congenital skeletal malformations (crooked calf disease) in calves . Thus, to minimize the risk of QA intoxication in livestock animals, only sweet lupins are listed as feed for livestock species in the catalogue of feed materials…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation